Saturated Control With Variable Prescribed Performance Applied to the Manipulator of UAV - Bu, Xiangwei (IEEE journal on miniaturization for air and space systems, 2023)
Variable prescribed performance control (PPC) is investigated for a type of nonlinear dynamic systems subject to actuator saturation, with an application to the manipulator of unmanned aerial vehicles (UAVs). Different from the current state-of-the-art, new performance functions are proposed to construct a variable prescribed funnel which is able to be readjusted according to the saturation situation. Furthermore, a new auxiliary system is developed to provide timely and bounded compensations on ideal control inputs. Thereby, the control singular problem associated with the existing PPC, caused by a saturated actuator, is effectively handled, and moreover, the addressed control protocol exhibits nonfragility to actuator saturation. In addition, the robustness of control is guaranteed via neural approximation. Finally, compared simulations on the manipulator of UAVs are presented to validate the design.